Neuropeptides in asthma, chronic obstructive pulmonary disease and cystic fibrosis - Atanasova, Kalina R. (Respir Res, 2018)
The nervous system mediates key airway protective behaviors, including cough, mucus secretion, and airway smooth muscle contraction. Thus, its involvement and potential involvement in several airway diseases has become increasingly recognized. In the current review, we focus on the contribution of select neuropeptides in three distinct airway diseases: asthma, chronic obstructive pulmonary disease (COPD), and cystic fibrosis. We present data on some well-studied neuropeptides, as well as call attention to a few that have not received much consideration. Because mucus hypersecretion and mucus obstruction are common features of many airway diseases, we place special emphasis on the contribution of neuropeptides to mucus secretion. Finally, we highlight evidence implicating involvement of neuropeptides in mucus phenotypes in asthma, COPD and cystic fibrosis, as well as bring to light knowledge that is still lacking in the field.